The Design of a Postgraduate Vocational Training Programme to Enhance Engineering Graduates' Problem-Solving Skills Through PBL - Miliou, Ourania; Ioannou, Andri; Georgiou, Yiannis; Vyrides, Ioannis; Xekoukoulotakis, Nikos; Willert, SØren; Andreou, Andreas S.; Andreou, Panayiotis; Komnitsas, Konstantinos; Zaphiris, Panayiotis; Yiatros, Stylianos (My University, 2022)
The current rapid technological advancements and the dynamic workplace environments call for engineering graduates to be equipped with a combination of interdisciplinary skills. Among the core skills for the engineering profession is problem-solving. Although industry professionals and academics consider problem-solving an essential attribute of engineers in industry 4.0, research shows that several engineering graduates are not adequately equipped to apply the problem-solving approach in workplace environments. During the past years, the most common approach referred to in the literature for enhancing problem-solving skills in engineering education is Problem-Based Learning (PBL). While research reported that PBL could improve students' skills in the early stage of higher education or within their degree programmes, most engineers generally accept that graduates will ''really'' learn how to be an engineer at the workplace. This paper reports on the methodological process of designing and developing a postgraduate vocational training programme to enhance engineering graduates' problem-solving skills through PBL. Specifically, it aims to investigate the programme's impact on engineering graduates' problem-solving skills and their perceptions about the PBL experience. A mixed-methods study was applied to answer the research questions. The Problem-Solving Inventory (PSI) was used to collect quantitative data regarding engineering graduates' problem-solving skills and semi-structured interviews were used to gather qualitative data regarding the implementation of the PBL programme. The results showed that the programme was successful in developing engineering graduates' problem-solving skills. Furthermore, engineering graduates reported several additional benefits regarding their learning experience. Examples include gaining a deeper understanding of the problem-solving process, developing professional knowledge, and enhancing employability potential. They also referred to various challenges which emerged during the programme, such as the time allocation for the assimilation of new knowledge, the application of problem-solving processes, and the communication with the technical staff in the workplace settings. We hope that this work can open a platform for discussion regarding the engineering curricula and the use of problem-oriented pedagogies toward improving employability and professional skills through industry-academia collaboration.
Keywords: engineering education; internship; problem-based learning; problem-solving; vocational training